2000
DOI: 10.1046/j.1365-2362.2000.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal triglyceride profiles in healthy normolipidemic male subjects are associated to insulin sensitivity, body composition and diet

Abstract: Diurnal TG profiles in healthy normolipidemic males are not age-dependent, but are associated to insulin sensitivity, fat mass and diet. Diurnal capillary TG profiles may be a valuable additional tool in estimating a risk profile for CHD since significant differences in diurnal TG are not always reflected by elevated fasting plasma TG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 46 publications
2
43
0
1
Order By: Relevance
“…Recently, a novel method has been developed to study diurnal TG profiles using repeated capillary self-measurements in an out-of-hospital situation, which correlates well with data obtained by standardized oral fat loading tests. 18,19 In a previous study using diurnal TG profiles, 18 healthy lean females showed lower diurnal TG profiles than males, in agreement with gender differences of postprandial lipemia reported by others. 12 In order to determine gender differences in diurnal TG profiles in overweight subjects, we compared diurnal triglyceridemia of overweight male and female subjects.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Recently, a novel method has been developed to study diurnal TG profiles using repeated capillary self-measurements in an out-of-hospital situation, which correlates well with data obtained by standardized oral fat loading tests. 18,19 In a previous study using diurnal TG profiles, 18 healthy lean females showed lower diurnal TG profiles than males, in agreement with gender differences of postprandial lipemia reported by others. 12 In order to determine gender differences in diurnal TG profiles in overweight subjects, we compared diurnal triglyceridemia of overweight male and female subjects.…”
Section: Introductionsupporting
confidence: 87%
“…18,19,21,22 Subjects were instructed to wash and dry their hands thoroughly before each measurement. With a lancing device, a drop of blood (30 ml) from the finger was obtained which was applied to the TG test strip in the TG analyzer.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, typical meal consumption in free-living subjects means that plasma TG concentrations progressively rise over the course of the day. 45 The bulk of this change in TG is a result of increases in chylomicron-TG and VLDL-TG concentrations (Figure 2). This rise reflects 'back-up' of clearance in TG-rich lipoproteins, which increases steadily, peaking at night at about 0200 hours, after which time plasma-TG concentrations fall steadily until morning.…”
Section: Quantity Of Isotope and The Food Vehiclementioning
confidence: 99%